2014
DOI: 10.2147/cia.s70359
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable effects of a low-threshold physical activity intervention on health-related quality of life in residential aged care

Abstract: BackgroundMobility is a main issue for health-related quality of life in old age. There is evidence for effects of physical activity (PA) interventions on several dimensions of health for the aged and also, some specific evidence for vulnerable populations, like residents of residential aged care. Research on low-threshold PA interventions for users of residential aged care and documentation of their sustainability are scarce. “Low threshold” implies moderate demands on the qualification of trainers and low fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 40 publications
1
33
0
1
Order By: Relevance
“…Two of them were large European multi-country studies that involved more than one CEE country [45,46]. Overall 152 reports on country level results were obtained: Austria (n=11) [47][48][49][50][51][52][53][54][55][56][57], Bulgaria (n=6) [45,46,58,59,13], Czech Republic (n=18) [60,61,45,46,[62][63][64][65][66]20,[67][68][69][70][71][72][73][74], Hungary (n=47) [11,75,76,45,[77][78][79][80][81][82][83][84][85][86]…”
Section: Search Resultsmentioning
confidence: 99%
“…Two of them were large European multi-country studies that involved more than one CEE country [45,46]. Overall 152 reports on country level results were obtained: Austria (n=11) [47][48][49][50][51][52][53][54][55][56][57], Bulgaria (n=6) [45,46,58,59,13], Czech Republic (n=18) [60,61,45,46,[62][63][64][65][66]20,[67][68][69][70][71][72][73][74], Hungary (n=47) [11,75,76,45,[77][78][79][80][81][82][83][84][85][86]…”
Section: Search Resultsmentioning
confidence: 99%
“…Relationships and interactions with other residents occurred primarily while the participants were engaged in planned NH activities. Therefore, it may be imperative for NH management teams and healthcare providers to develop strategies that include the provision of support in accessing activities and opportunities to participate in them (e.g., low‐threshold group exercise programs), to help NH residents, including those with ambulatory dysfunctions, to engage in activities (Quehenberger, Cichocki, & Krajic, ). In a previous study, older adults in NHs experienced a deep sense of loss and loneliness because of the frequent turnover of nurses in the NHs, as they perceived the relationships with nurses as very important and meaningful in their lives (Chang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the prominence of these domains, it has been observed that interventions aimed at the promotion of physical activity during old age present positive results although with low frequency [36].…”
Section: Discussionmentioning
confidence: 99%